Determinants of Poverty in Indonesia: A Dynamic Panel Analysis of Economic and Social Factors across 20 Provinces - Prawoto, Nano (Balance : Jurnal Akuntansi dan Manajemen, 2024)
This study aims to analyze the influence of economic growth, population, general allocation funds (DAU), education budget, and foreign direct investment (FDI) on the number of poor people in 20 provinces in Indonesia in the 2012-2022 period. The analysis tool used in this study is the dynamic panel regression approach. This study found that in the short term, the number of people and DAU had a positive effect on the increase in the number of poor people, while the education and FDI budgets had a negative impact, reducing the number of poor people. In the long run, economic growth, population growth, and FDI have been shown to have a significant effect on reducing poverty rates. These findings provide important insights for government economic policy, which needs strengthen effective allocation of funds and focus on improving the quality of education and improving the investment climate to drive inclusive economic growth. In addition, policies that promote foreign investment and more efficient management of DAU can accelerate the poverty alleviation process in Indonesia.